(untitled) - Koenig, Eldo C. (Hoboken, N.J, 2007)
A comprehensive look at General automata and how it can be used to establish the fundamentals for communication in human-computer systems Drawing on author Eldo C. Koenig's extensive expertise and culling from his thirty-four previously published works, this seminal resource presents knowledge structures for communication in Human-Computer Systems (HCS) based on General automata. The resulting model provides knowledge representations for software engineering.
Keywords: Human-computer interaction,Machine theory,Giao tiếp giữa con người và máy tính,Lý thuyết máy; Mathematical models,Mô hình toán học